THE CONCEPT OF "CULTURE" IN TRANSLATION STUDIES (Conferencea, 2022)
In recent years, there has been a growing focus on the relationship between culture and translation. This is because most scholars emphasize in their work that it is effective to consider the issues of culture and translation together, in an interconnected way. For example, L.V. Kushnina studies translation as a self-evolving and self-organizing system in the process of interaction of languages and cultures (Kushnina: 2004, 22-24). The researcher examines the nature of meaning, identifying ways to “harmonize” text content in different languages and cultures. In viewing the interdependence of language, translation, and culture, it was appropriate to focus on the definition of the concept of “harmonization of the translated text” and to define the interrelationship of its concepts of equivalence and adequacy.